Nusyuz of Husband and Wife in the Maslahah Perspective - Apriyanti, Apriyanti; Uswatun Hasanah (Nurani, 2025)
Nusyuz often arises when the relationship between a husband and wife loses its harmony. This can lead to prolonged disputes, known as shiqaq, and may even contribute to situations of domestic violence, where the wife is often the one who suffers the most. This article is intended to examine the maslahah aspects contained in nusyuz, both those carried out by husbands and wives in the household. Through the principle of maslahah, nusyuz can not only be resolved but also anticipated and prevented before it arises. Prevention will be easier to do than handling when nusyuz has occurred. This research is normative by using an Islamic legal approach, namely maslahah. The research data comes from the books of ushul al-fiqh, fiqh, tafsir, and other references such as books and articles related to the research theme. All data will be analyzed using descriptive analytic. The findings reveal that nusyuz is a form of disobedience that can be committed by either the husband against his wife or the wife against her husband. The absence of a firm prohibition from the Koran and hadith against nusyuz, does not make its is haram. However, avoiding nusyuz must be done by husband and wife because it is one of the efforts to create benefits. A mutually open attitude between husband and wife through good communication, being able to regulate emotions, carrying out rights and obligations, and avoiding attitudes of superiority, selfishness, authoritarianism and violence towards husband and wife must be carried out so that nusyuz can be avoided and prevented. Making every effort to prevent nusyuz signifies the realization of maslahah, ensuring the well-being and harmony of the marital relationship.